Correlates of elevated blood pressure in healthy children: a systematic review. Issue 5 (31st July 2018) - Fowokan, A. O.; Sakakibara, B. M.; Onsel, N.; Punthakee, Z.; Waddell, C.; Rosin, M.; Lear, S. A.
Summary: The prevalence of hypertension in children is increasing globally. Addressing this will require a robust understanding of associated risk factors. To this end, we conducted a systematic review to identify correlates of elevated blood pressure (BP) in children. Literature searches were conducted using pre‐defined search terms from three academic databases. The abstract and full text of identified studies were screened for eligibility by two independent reviewers. A total of 100 studies were included in this systematic review. An assessment tool was first used to assess study quality; a narrative synthesis was then performed. We found a broad range of physiological, social and behavioural factors associated with elevated BP in children. The most common correlate observed was adiposity, suggesting that childhood obesity may be implicated in the increased prevalence of hypertension observed in children. However, the broad range of other factors identified underscores the multi‐factorial aetiology of hypertension. Data from a broad range of studies showed that the correlates of hypertension in children are multi‐factorial. Therefore, approaches aimed at preventing hypertension must in turn be multi‐factorial to ensure that the burden of hypertension in childhood is addressed.